REPAIR OF FLEXURAL DAMAGED REINFORCED CONCRETE BEAMS USING EMBEDDED BAMBOO REINFORCED EPOXY COMPOSITE (Malaysian Journal of Civil Engineering, 2020)
In recent years, repair and retrofit of existing structures such as buildings and bridges have been among the most important challenges in Civil Engineering. Strengthening reinforced concrete (RC) members with steel plates is a conventional method that has been adopted for decades. The corrosive nature of steel plates, its weight and the need for many anchor bolts for attachment makes it inefficient for retrofitting damaged structures. Thus, there is a need to source for an alternative material which does not corrode and still be used in the strengthening of reinforced concrete. Bamboo Reinforced Epoxy Composite (BREC) was used to repair five (5) damaged reinforced concrete beams in this research. Two of the beams were preloaded to 40 % and 60 % of the ultimate load before strengthening with BREC and all the beams were loaded to failure. The RC beams implanted with BREC rods experienced a rise in their load carrying capacity when tested. Beams preloaded up to 40 % and 60 % had an increase in flexural strength of 33.7 % and 39.3 % respectively when compared with beams reinforced with steel reinforcements. BREC rods in concrete is an effective method in increasing the flexural strength of RC beams.